QR Code-Based Picture Story Book Media to Improve Analytical Thinking on Elemental Materials in Class 5 Literary Work at State 4 Purwodadi Primary School Malang District - Dwi Yoni Hidayati; Cindya Alfi; Mohamad Fatih (Universitas Muhammadiyah Enrekang, 2024)
A country needs to invest in its education. Without education, the people of the country will not understand what independence means. The public education system in this country will be run independently. Apart from that, the people will also have superior qualities that will be beneficial for the country. However, based on empirical data in this sector, there are limitations in the use and accessibility of learning media. Teachers will actually benefit from developing learning media because they will be better able to explain subject matter to students. Therefore, this research was conducted at SD Negeri 4 Purwodadi, Malang Regency. One type of research and development (R&D) is this research. The Borg and Gall research model was used in this research. The research findings are based on material expert scores which are considered